Soviet metal-fabricating and economic development : practice versus policy - Granick, David (Madison : University of Wisconsin Press, 1967)
This book concentrates on the metal-fabricating industries of the USSR and particularly on their development during the first two five year plans of 1928-1937. It describe solutions which have been implemented within the Soviet Union and to evaluate the success of these solutions.
Includes index.
Includes bibliographical references: p. 349-355.
occ 17/01/2019
Loans
Keywords: Metal trade; Machinery industry; Soviet Union